2008
DOI: 10.1128/jcm.00813-08
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Escherichia coli Strains Causing Acute Cystitis in Women and the Fecal E. coli Population of the Host

Abstract: Previous epidemiological assessments of the prevalence versus special-pathogenicity hypothesis for urinary tract infection (UTI) pathogenesis in women may have been confounded by underlying host population differences between women with UTI and healthy controls and have not considered the clonal complexity of the fecal Escherichia coli population of the host. In the present study, 42 women with acute uncomplicated cystitis served as their own controls for an analysis of the causative E. coli strain and the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
123
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 25 publications
21
123
1
Order By: Relevance
“…The aerobactin prevalence in E. coli strains is also highly variable in the literature, from 26% to 85% (5,11,13,15,28,39,40). In this study, the prevalence of aerobactin was up to 28% but not significantly different between the PN and Cys isolates, coinciding with some reports (11,15) but not with others (5,13).…”
Section: Discussionsupporting
confidence: 75%
“…The aerobactin prevalence in E. coli strains is also highly variable in the literature, from 26% to 85% (5,11,13,15,28,39,40). In this study, the prevalence of aerobactin was up to 28% but not significantly different between the PN and Cys isolates, coinciding with some reports (11,15) but not with others (5,13).…”
Section: Discussionsupporting
confidence: 75%
“…This factor occurred in 92 (98%) FeEC isolates as seen in Table 2. Similar results were obtained by previous studies, 18,19 whereas the frequency of the iha gene, as other adhesion, was 26% (24/94). Our laboratory previously showed that the prevalence of iha gene was 29% among UPEC isolates.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of our study indicated that the presence of the hlyA and cnf1 genes was 10% and 3% respectively. In an other study, Usein et al 21 demonstrated that the hlyA and cnf1 genes were found in 35% of E. coli bacteria recovered from the fecal flora of healthy adult humans. The results showed the variation geographical distribution of these genes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, a spectrum of comorbidities due to cystitis, prostatitis, pyelonephritis, urethritis and a few more are found associated with acute cases of UTI [5] . Most genital-associated infections are caused by the retrograde ascent of bacteria from fecal flora via urethra to bladder and kidney, in females [6] .…”
Section: Introductionmentioning
confidence: 99%